2013
DOI: 10.1111/medu.12081
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of perceived effects of innovations in postgraduate medical education

Abstract: These outcomes are in line with theoretical notions regarding innovations in general and may be helpful in the implementation of other innovations in PGME. Given the substantial effects of innovations outside the strictly education-related domain, individuals designing and implementing innovations should consider all potential effects, including those identified in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 27 publications
1
54
0
1
Order By: Relevance
“…[23242526] This strategy of integrating information can help students establish fully automated schemas for understanding human disease and health during medical school. [27282930313233]…”
Section: Discussionmentioning
confidence: 99%
“…[23242526] This strategy of integrating information can help students establish fully automated schemas for understanding human disease and health during medical school. [27282930313233]…”
Section: Discussionmentioning
confidence: 99%
“…However, throughout this study, as with others,7 9 it became clear that while WBA has become realised as a component of training, it is as yet difficult to evaluate the impact of this innovation on the learning trajectories of trainers and trainees. The limited exposure and varying WBA experiences encountered in this study limit our ability to interpret and plot (or track) complete trajectories arising from these experiences.…”
Section: Discussionmentioning
confidence: 78%
“…But how these WBAs play out in actual practice remains unclear, partly as a result of the varied ways in which the tools have been implemented; research continues to highlight the consistent ‘tick-box’ approach to completion, concerns around relevance and responsibility6–8 and issues of implementation and acceptability 9 10. In attempting to evaluate the impact or effectiveness of WBA, a number of systematic reviews have concluded that WBA does not affect a demonstrable change in practice 11 12.…”
Section: Introductionmentioning
confidence: 99%
“…17 The successful implementation of an innovation depends on users' affinity with the innovation and its incorporation into workplace routines. 29 The lack of full incorporation of the generic competencies in the daily workplace could have resulted in the limited use of generic competencies during entrustment decisions.…”
Section: Discussionmentioning
confidence: 99%